Degradation issues of PEM electrolysis MEAs. (August 2018) - Siracusano, S.; Van Dijk, N.; Backhouse, R.; Merlo, L.; Baglio, V.; Aricò, A.S.
Abstract: One of main challenge of proton exchange membrane (PEM) water electrolysis is the achievement of a long-term durability exceeding 100 khours. Accordingly, degradation mechanisms of membrane electrode assemblies (MEAs) and stack components of PEM electrolysers deserve large attention. An important objective of the EU ELECTROHYPEM project was to develop components for PEM electrolysers with enhanced activity and stability in order to reduce stack and system costs and to improve efficiency, performance and durability. The focus of the project was concerning mainly with electrocatalysts and membranes development and validation of these materials in a PEM electrolyser. In this work, a first set of MEAs, used for 3500–5700 h in a PEM electrolyser, was investigated using electrochemical and physico-chemical techniques. The goal was to individuate key degradation issues and to provide a reliable estimation of the MEA endurance under real life operation. Specific approaches to mitigate the degradation mechanisms are discussed. Highlights: Degradation mechanisms of MEAs components of PEM electrolysers was investigated. Mitigation strategies to reduce MEA degradation have been discussed. A stack based on advanced components was demonstrated in the Electrohypem Project.